Removal of intracardiac bone cement embolism after percutaneous kyphoplasty: A case report. Issue 11 (March 2020) - Song, Yu; Huang, Xiaofan; Wu, Long
Abstract: Rationale: Leakage of bone cement is a common complication after percutaneous kyphoplasty. In rare cases, bone cement can leak into the venous system, which can be life threatening, especially when it causes an embolism in the heart. Patient concerns: A 79-year-old female patient developed chest pain with chest tightness 3 weeks after the percutaneous kyphoplasty. Diagnoses: Initially, negative fluoroscopy results and elevated myocardial enzymes suggested that the patient's chest pain and chest tightness symptoms were manifestations of coronary heart disease. However, in the subsequent computed tomography (CT) examination, foreign bodies in the heart and pulmonary vessels were found. Interventions: The patient underwent emergency surgery to remove the bone cement and repair the tricuspid valve. Outcomes: The postoperative course was uneventful and the patient was discharged on the 13th day after surgery. Lessons: If a patient develops chest pain with chest tightness after percutaneous kyphoplasty, the clinicians must be vigilant and take into account the limited sensitivity of fluoroscopy and use chest computer tomography and echocardiogram as the first choice and thereby prevent serious consequences.